Respostas
respondido por:
10
y² + 7y + 6 = ( y + 1) ( y + 6)
y + 1 =0 y + 6 = 0
y = -1 y = -6
x² + 11x + 10 = ( x + 1)(x + 10)
x + 1 = 0
x = -1
x + 10 = 0
x = -10
Espero ter ajudado, bons estudos. Abraços
y + 1 =0 y + 6 = 0
y = -1 y = -6
x² + 11x + 10 = ( x + 1)(x + 10)
x + 1 = 0
x = -1
x + 10 = 0
x = -10
Espero ter ajudado, bons estudos. Abraços
fatimacmarconi:
sem problemasd minha flor
x - 1 = 0
x = 1
x - 6 = 0
x = 6
respondido por:
6
Espero ter ajudado...
(x+9)(x+4) -->
X+9=0---> x=-9
X+4=0---> x=-4
S={-9;-4}
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás